Hormone, Targeted, and Combinational Therapies for Breast Cancers: From Humans to Dogs - Ke, Chiao-Hsu; Lin, Chao-Nan; Lin, Chen-Si (International journal of molecular sciences, 2024)
Breast cancer (BC) is the most frequent cancer in women. In female dogs, canine mammary gland tumor (CMT) is also the leading neoplasm. Comparative oncology indicates similar tumor behaviors between human BCs (HBCs) and CMTs. Therefore, this review summarizes the current research in hormone and targeted therapies and describes the future prospects for HBCs and CMTs. For hormone receptor-expressing BCs, the first medical intervention is hormone therapy. Monoclonal antibodies against Her2 are proposed for the treatment of Her2+ BCs. However, the major obstacle in hormone therapy or monoclonal antibodies is drug resistance. Therefore, increasing alternatives have been developed to overcome these difficulties. We systemically reviewed publications that reported inhibitors targeting certain molecules in BC cells. The various treatment choices for humans decrease mortality in females with BC. However, the development of hormone or targeted therapies in veterinary medicine is still limited. Even though some clinical trials have been proposed, severe side effects and insufficient case numbers might restrict further explorations. This difficulty highlights the urgent need to develop updated hormone/targeted therapy or novel immunotherapies. Therefore, exploring new therapies to provide more precise use in dogs with CMTs will be the focus of future research. Furthermore, due to the similarities shared by humans and dogs, well-planned prospective clinical trials on the use of combinational or novel immunotherapies in dogs with CMTs to obtain solid results for both humans and dogs can be reasonably anticipated in the future.